2020
DOI: 10.1016/j.hemonc.2020.07.005
|View full text |Cite
|
Sign up to set email alerts
|

The risk and prognosis of COVID-19 infection in cancer patients: A systematic review and meta-analysis

Abstract: Numerous studies have been published regarding outcomes of cancer patients infected with the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) virus causing the coronavirus disease 2019 (COVID-19) infection. However, most of these are single-center studies with a limited number of patients. To better assess the outcomes of this new infection in this subgroup of susceptible patients, we performed a systematic review and meta-analysis to evaluate the impact of COVID-19 infection on cancer patients. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
105
2
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(133 citation statements)
references
References 35 publications
(43 reference statements)
5
105
2
7
Order By: Relevance
“…Higher fatality and hospitalization rates for COVID-19 patients with a previous diagnosis of cancer have been observed in several studies [11][12][13][14][15][16][17] , including a recent large registry-based Italian study. 11 Instead, we did not find any studies comparing the risk of SARS-CoV-2 infection and COVID-19 death in cancer survivors with that in the general population.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Higher fatality and hospitalization rates for COVID-19 patients with a previous diagnosis of cancer have been observed in several studies [11][12][13][14][15][16][17] , including a recent large registry-based Italian study. 11 Instead, we did not find any studies comparing the risk of SARS-CoV-2 infection and COVID-19 death in cancer survivors with that in the general population.…”
Section: Discussionmentioning
confidence: 93%
“…Only a few case series tried to infer the risk of infection, comparing the prevalence of SARS-CoV-2 infection in cancer patients with that in health care providers 12 or with that in the general population, [13][14][15] or comparing the prevalence of cancer among COVID-19 patients with that in the general population. 16 These studies gave inconsistent results. 12,17 The observed lower probability of being tested and of testing positive could be related to protective behaviours adopted early by people with previous cancer, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 Since then, several systematic reviews have attempted to assess the impact of cancer on COVID-19 severity and mortality. [6][7][8] However, these studies have been limited by their inclusion criteria, small subgroups of the population, and case duplications. 9 Subsequently, these often lacked the details regarding cancer or cancer treatment and short-term mortality data.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to the general population patients who had no recent chemotherapy exposure had a similar to modestly increased risk of ICU admission or death [5]. Two meta-analyses show case fatality rates (CFR) following COVID-19 of approximately 21-22% in patients with cancer compared to 5.9% in non-cancer patients [8,9]. However, a notable exception is a study from two New York hospitals that included 585 COVID-19 patients and found a similarly high CFR of 25% for patients with cancer and a CFR of 21% for age-sex-comorbidity matched COVID-19 non-cancer patients [10].…”
Section: Editorialmentioning
confidence: 99%